Ukraine : Request for Extended Arrangement Under the Extended Fund Facility and Cancellation of Stand-By Arrangement. (IMF Staff Country Reports; Country Report, 2015)
This paper discusses Ukraine's Request for Extended Arrangement Under the Extended Fund Facility (EFF) and Cancellation of Stand-by Arrangement (SBA). Despite tangible progress under the SBA, the crisis in Ukraine has increased its balance of payments and adjustment needs beyond what can be achieved under the current program. The authorities' new four-year IMF-supported program aims to decisively address these challenges. The program lays out a strategy to restore financial and economic stability and resolve long-standing structural obstacles to growth. In view of Ukraine's large external financing needs and the authorities' strong policy commitments, the IMF staff supports approval of Ukraine's four-year Extended Arrangement under the EFF with access equivalent to SDR 12.348 billion.